Profil Fitokimia dan Aktivitas Antioksidan Ekstrak Etanol Daun Jambu Mete (Anacardium Occidentale Linn) (International Forum of Researchers and Lecturers, 2024)
Cashew leaves or also called monkey guava are known by many people, especially in Southeast Sulawesi and are believed to have a number of health benefits but are still rarely known by some people. This study aims to determine the profile of secondary metabolite content and determine the antioxidant activity of ethanol extract of cashew leaves (Anacardium occidentale Linn) using the extraction method by maceration. The extraction process of old cashew leaves is carried out by the maceration method using 96% ethanol solvent for 3 days of soaking and stirring every 24 hours, then concentration is carried out through the evaporation process. Phytochemical testing includes identification of alkaloids, flavonoids, polyphenols, tannins, steroids/triterpenoids and saponins, as well as testing antioxidant activity using the DPPH method (1,1-diphenyl-2-picrylhydrazyl). The results showed that the extract of cashew leaves (Anacardium occidentale Linn) strongly positive contains phenolic compounds, flavonoids, steroids and saponins. Based on the results of the IC50 calculation, 96% ethanol extract has the highest antioxidant activity at a concentration of 14.35 ppm (µg/mL) with a very high category. The content of secondary metabolites and very high antioxidant activity from the results obtained, explain that cashew nuts have the potential to increase body immunity and can be used in various antioxidant food products so that cashew leaves are more economically valuable for the community.